Metabolomics-Based Pharmacodynamic Analysis of Zhuang Yao Shuang Lu Tong Nao Granules in a Rat Model of Ischemic Cerebral Infarction. (5th July 2022) - Zhai, Yang; Chen, Yangling; Luo, Yihui; Mei, Xiaoping; Wu, Lin; Mo, Xueni; Zou, Min; Zhou, Mingzhao; Wu, Yangling; Zheng, Guangshan; Yang, Peng; He, Qingyu; et al.
Abstract : This study used a metabolomic approach to reveal changes in the levels of metabolic biomarkers and related metabolic pathways before and after Zhuang Yao Shuang Lu Tong Nao granule (YHT) treatment in rats with cerebral ischemia. The neurological deficit scores were significantly higher in the MCAO_R group than in the NC group, indicating that the mice had significantly impaired motor functions. The YHT group had significantly lower scores than the MCAO_R group, suggesting that YHT significantly improved motor function in rats. TTC staining of the brain tissue revealed that YHT significantly reduced the area of cerebral infarction in the treated rats. The MCAO_R group was better separated from the NC rent, sham, and YHT groups via metabolomic PCA. Moreover, there were significant differences in the differential metabolites between the MACO_R and YHT groups. Eighteen common differential metabolites were detected between the MACO_R and NC groups, MACO_R and sham groups, and MACO_R and YHT groups, indicating that YHT significantly increased the levels of various metabolites in the serum of cerebral ischemic stroke (CIS) rats. Moreover, a total of 23 metabolic pathways were obtained. We identified 11 metabolic pathways with the most significant effects in the bubble plots. In conclusion, from a systems biology perspective, this metabolomics-based study showed that YHT could be used to treat ischemic stroke by modulating changes in endogenous metabolites.